EXTRACTION OF BIOLOGICALLY ACTIVE COMPONENTS FROM FRESHWATER SAPROPEL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Sapropel has been used for different purposes - in agriculture as fertilizer, in construction as building material, in cosmetic products, in balneology also in medicine and pharmaceuticals as bioactive component. Previously sapropel has been commonly used in raw form and there is no general accepted method or standard method for obtaining sapropel extract. However, most extraction methods follow the same path. Currently, there are few extraction methods using several extractants for obtaining bioactive components from raw sapropel. The most commonly used extractant is alkaline solution. When sapropel is subjected to alkaline environment, the humic and fulvic acids, together with some lipids, vitamins and sugar, present in the raw sapropel become soluble, however other organic and mineral content present in the sapropel remain solid. Alkaline extraction is followed by filtration and water present in the aqueous mixture is evaporated off. Latvian freshwater sapropel can be used as raw material for obtaining sapropel extract and use it as remedy. But the main question for sapropel usage in medicine, balneology and pharmacy is to develop quality criteria for raw sapropel and its extracts. The quality criteria should include minimum requirements for biologically active substance concentration, pH values, antioxidants as well as physical characteristics. In future studies the differences in extract characteristics of the various deposit sites, as well as the stability of the extracts under different storage conditions should be defined; also, there is need for a common approach to develop method of extraction process for active substances from sapropel and analysis procedures of its extract.